2021
DOI: 10.1016/j.asmr.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Tenotomy or Tenodesis for Tendinopathy of the Long Head of the Biceps Brachii: An Updated Systematic Review and Meta-analysis

Abstract: The purpose of this meta-analysis was to provide an up-to-date comparison of clinical outcomes of tenotomy and tenodesis in the surgical treatment of long head of the biceps brachii (LHB) tendinopathy. Methods: A literature search was conducted in EMBASE, Pubmed/Medline and the Cochrane database from January 2000 to May 2020. All studies comparing clinical outcomes between LHB tenotomy and tenodesis were included. Quality was assessed using the Coleman score. Results: We included 25 studies (8 randomized studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
1
14
1
5
Order By: Relevance
“…Portanto, para que a estabilização ocorra, é necessário equilíbrio entre forças estáticas e dinâmicas que atuam sobre o ombro, o qual se dá maioria das lesões ocorre devido à degeneração e após ruptura do tendão supra-espinal 1 . O tratamento consiste inicialmente em abordagem conservadora com fisioterapia; em alguns casos, em que ocorre degeneração ou luxação do tendão, está indicado procedimento cirúrgico com debridamento artroscópico combinado à tenotomia ou tenodese do músculo 1,8 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Portanto, para que a estabilização ocorra, é necessário equilíbrio entre forças estáticas e dinâmicas que atuam sobre o ombro, o qual se dá maioria das lesões ocorre devido à degeneração e após ruptura do tendão supra-espinal 1 . O tratamento consiste inicialmente em abordagem conservadora com fisioterapia; em alguns casos, em que ocorre degeneração ou luxação do tendão, está indicado procedimento cirúrgico com debridamento artroscópico combinado à tenotomia ou tenodese do músculo 1,8 .…”
Section: Resultsunclassified
“…A tenossinovite do músculo bíceps braquial é lesão altamente prevalente em pacientes com dor anterior e profunda do ombro 8 . Afeta o tendão da porção longa do músculo no seu trajeto intra-articular, com ocasional degeneração e ruptura.…”
unclassified
“…Recently, 7 systematic reviews have been performed comparing biceps tenotomy versus tenodesis. 2,4,15,17,22,24,30 Most of these reviews did not demonstrate a significant functional difference between these 2 procedures. Popeye deformity and cramping were more common after tenotomy than with tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several meta-analyses have been published on the topic of surgical treatments for the long head of biceps. [44][45][46][47][48][49][50] These studies are all limited to some extent, with some disagreement in their findings. Dekker et al reviewed cadaveric studies and demonstrated no difference in ultimate load to failure in various fixation types including screws and anchors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several meta-analyses have been published on the topic of surgical treatments for the long head of biceps 44–50. These studies are all limited to some extent, with some disagreement in their findings.…”
Section: Discussionmentioning
confidence: 99%